2010
DOI: 10.1007/s11431-010-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of dodecagonal pyramid on nitrogen face GaN and its effect on the light extraction

Abstract: Wet etching has been widely used in defect evaluation for Ga-face GaN and surface roughness for N-face GaN dodecagonal pyramids has been fabricated on laser-lift-off N-face GaN by hot phosphor acid etching. The dodecagonal pyramid shows twelve facets including six {20-2-3} and six {22-4-5} planes. From cross-sectional TEM image, it is shown that the pyramid corresponds to the top of the edge dislocation. Compared with hexagonal pyramid-surface light emitting diodes (LEDs) etched by commonly used photoelectroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, according to Eqs. (6) and (7) and the activation energy in KOH, we obtained above (0.73 eV), c ER between etching KOH and H 3 PO 4 (353 K) is calculated enormous high to $5.32 Â 10 12 . It quite contradicts with the experiment results from which c ER (353 K) is calculated to be in the range of (10,200).…”
Section: B Ecmentioning
confidence: 69%
See 2 more Smart Citations
“…However, according to Eqs. (6) and (7) and the activation energy in KOH, we obtained above (0.73 eV), c ER between etching KOH and H 3 PO 4 (353 K) is calculated enormous high to $5.32 Â 10 12 . It quite contradicts with the experiment results from which c ER (353 K) is calculated to be in the range of (10,200).…”
Section: B Ecmentioning
confidence: 69%
“…6,7 It is attributed to the facet-selective etching due to the competition between facets that have different surface energy and etching rates. However, we found that it was the dislocation serving as the preferential spatial site for pyramids evolvement initiated the etching process and accelerated the dissociation.…”
Section: D-ds Selective Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…For hexagonal facets of {10-1-1}, the direction of the edge projection is ,11-20.. As a result, we set the directions of O9A, O9C as [2-1-10] and [11][12][13][14][15][16][17][18][19][20], O9B as . In the triangle AO9B, a 1 9 and a 2 9 correspond to the angles Y and w, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…11 In our previous work, we observed dodecagonal pyramids on N-polar GaN and concluded that thermodynamics and kinetics related factors led to the formation of the pyramids. 3,12 Hot H 3 PO 4 etching is more kinetic-limited than KOH etching. The crystallographic planes of the pyramids are not stable, and the oblique angles between the etched facets and the base plane are varied from 44u-52u.…”
Section: Introductionmentioning
confidence: 99%